2018
DOI: 10.1111/jam.14119
|View full text |Cite
|
Sign up to set email alerts
|

Impact of probiotic Lactobacillus sp. on autochthonous lactobacilli in weaned piglets

Abstract: Aims: This study aimed to determine whether host-adapted lactobacilli exhibit superior survival during intestinal transit relative to nomadic and free-living organisms, and to characterize the impact of probiotic lactobacilli on autochthonous lactobacilli. Methods and Results: Mixed cultures of Lactobacillus casei K9-1 and Lactobacillus fermentum K9-2, or reutericyclin producing Lactobacillus reuteri and its isogenic mutant were fed to piglets as freeze-dried culture, or as part of fermented feed. Lactobacilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…A number of gut bacteria have been identified for their beneficial or harmful physiological functions. Colonization and changes in beneficial functional microbes (e.g., Lactobacillus and Prevotella) have great potential to contribute to feed intake, feeding efficiency, obesity, and muscle growth of pigs at a specific time (24,28,29). Conversely, the invasion by harmful bacteria (e.g., Erysipelotrichaceae) is threats to host health (30).…”
Section: Discussionmentioning
confidence: 99%
“…A number of gut bacteria have been identified for their beneficial or harmful physiological functions. Colonization and changes in beneficial functional microbes (e.g., Lactobacillus and Prevotella) have great potential to contribute to feed intake, feeding efficiency, obesity, and muscle growth of pigs at a specific time (24,28,29). Conversely, the invasion by harmful bacteria (e.g., Erysipelotrichaceae) is threats to host health (30).…”
Section: Discussionmentioning
confidence: 99%
“…Strain-specific qPCR demonstrated that the millet malt is a main source of mahewu microbiota. Strain-specific primers have previously been used for strain-specific quantification of bifidobacteria and lactobacilli in fecal samples (44,45). Past studies on molecular source tracking of food microbiota used RAPD PCR or repetitive element sequence-based PCR to trace the origin of lactic acid bacterial strains in sourdoughs; however, the low specificity of these techniques did not provide conclusive evidence on strain identity (18,46).…”
Section: Discussionmentioning
confidence: 99%
“…Overnight cultures of L. reuteri TMW1.656, L. reuteri TMW1.656 rtcN, L. casei K9-1, and L. fermentum K9-2 were applied for feed fermentation; a detailed characterization of the feed fermentation and the microbiological characteristics of the feed is provided by Zhao et al (2018). Significant components of the dietary treatments are listed in Table 1.…”
Section: Experimental Diets and Animalsmentioning
confidence: 99%
“…Host-adapted lactobacilli that are stable members of the intestinal microbiota of swine include Limosilactobacillus reuteri (previously Lactobacillus reuteri, Zheng et al, 2020) and Lactobacillus amylovorus (Leser et al, 2002;Duar et al, 2017a); nomadic organisms with documented use as probiotics in swine include Lactiplantibacillus plantarum, Limosilactobacillus fermentum, and Lacticaseibacillus rhamnosus (previously all assigned to the genus Lactobacillus, Zheng et al, 2020). Recent studies suggest that host-adapted and nomadic probiotics differ with respect to their survival in the intestinal tract, and with respect to mechanisms of probiotic activity (Maldonado-Gómez et al, 2016;Walter et al, 2018;Zhao et al, 2018;. Probiotic feeding of the host adapted L. reuteri TMW1.656 resulted in significantly higher cell counts of the probiotic strain during intestinal transit when compared to the nomadic organisms L. fermentum K9-2 and Lacticaseibacillus casei K9-1 that were provided at the same viable cell counts (Zhao et al, 2018), suggesting improved survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation